Effect of sugars, growth regulators and amino acids on in vitro sporangial germination of pearl millet downy mildew - D.P. THAKUR, S. APPAJI and (Indian Phytopathology, 2002)
Sporangia, the asexual phase of the pathogen Sclerospora graminicola, the causative agent of pearl millet downy mildew, form an important source in the epidemiology of the disease. They germinate in medium conducive for them and in nature, they need moisture to germinate and infect. In vitro experimental results indicated that sugars did not induce germination. Glucose was found to show least inhibitory effect. The growth regulators IAA and NAA inhibited the sporangial germination to satisfactory levels whereas maleic hydrazide, 2, 4-D and GA did not. Among the selected amino acids, L-glutamic acid induced sporangial germination of a higher order unlike L-leucine which proved inhibitory.